Liikuntaorganisaatioiden ympäristöhallinnan alueellinen kehittämisprosessi : ohjelmateorian muodostaminen Pohjois-Karjalan liikuntaorganisaatioille kehittävän arvioinnin menetelmään pohjautuen - Rajala, Laura (2024)
The degradation of the natural environment and the climate crisis are among the most relevant challenges facing our society on a global level. Meeting these challenges is one of the key developments of the current decade. The European Union is aiming for the status of a carbon- neutral continent by 2050, and the Finnish state is committed to the pursuit of carbon neutrality by 2035. As part of society, the sports sector is equally dependent on the conditions of the natural environment as well as being involved in their deterioration. This Master's thesis is positioned in the sociological research line of environmental management. The research line is growing, but research on evaluation and cooperation is still scarce. The aim of this study is to form a program theory to support the co-development of the regional environmental management of sports organizations. The research focused on third and public sector organisations operating in North Karelia and the operational methods of cooperation they used to promote environmental management. The focus of the study was to find out what kind of measures and cooperation models of different actors would be needed to promote environmental management in the target area. The material was collected through group interviews in the spring of 2022, in which a total of 16 people participated. The groups were composed of experts representing actors from different sectors from the same area. The interviews were transcribed and analyzed using theory-directed content analysis. Based on the results of content analysis formed on the framework for developing environmental management, program theory was created based on methods of developing evaluation. The central result of the content analysis was that networks for co-development exist. However, they are not used to promote environmental management. As far as environmental management was concerned, cooperation was still mainly limited, but it was recognized that it would work to launch it in the existing networks. The practices of environmental management in organizations were varied. In order to enable co-development, it would be essential to create a common regional operating culture. It should be based on shared strategic objectives, the realisation of which could be promoted, for example, by means of resource steering. Based on content analysis and processed literature, the conclusion was formed as program theory, a model of change for regional environmental management.